2018
DOI: 10.1007/s00138-018-0984-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-parameter optimization tools comparison for multiple object tracking applications

Abstract: Commonly, when developing an algorithm it is necessary to define a certain number of variables that control its behavior. Optimal parameters result in better performance that could translate into profits for companies, stand out among similar applications or better ranking on algorithm competitions. However, it is not a simple task to find the combination of parameters that provides the best results. Manual tuning could be a stressful and difficult task even for expert users. In this paper we present, evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Bergstra et al [41] quickly followed with an alternative approach that they called TPE. A comparison between several data sets showed that the performance of such a hyper-parameter optimization technique varies with each setup [42][43][44]. This research topic is often referred to as hyper-parameter optimization and is the subject of active research and development [44][45][46].…”
Section: Relationship Between Hyper-parameter Optimization and Simulation-based Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Bergstra et al [41] quickly followed with an alternative approach that they called TPE. A comparison between several data sets showed that the performance of such a hyper-parameter optimization technique varies with each setup [42][43][44]. This research topic is often referred to as hyper-parameter optimization and is the subject of active research and development [44][45][46].…”
Section: Relationship Between Hyper-parameter Optimization and Simulation-based Optimizationmentioning
confidence: 99%
“…In the past several years, many newly developed hyper-parameter optimization approaches have advanced the field. Studies such as [42][43][44] have empirically compared different meta-heuristics. This approach is the key to identifying characteristics of each meta-heuristic, which, in turn, can result in the recommendation of one meta-heuristic.…”
Section: Relationship Between Hyper-parameter Optimization and Simulation-based Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergstra et al [36] quickly followed with an alternative approach and called it TPE. A comparison between several data-sets showed that the performance of such a hyper-parameter optimization technique varies with each setup [37][38][39]. The research topic is often referred to as hyper-parameter optimization and is subject to active research and development [39][40][41].…”
Section: Relationship Between Hyperparameter-optimization and Simulatmentioning
confidence: 99%
“…Comparison studies such as [37][38][39] are very crucial to identify strengths and weaknesses of these approaches. Sörensen [42] admonishes that the design and application of new meta-heuristics should go beyond playing a simple up-the-wall game.…”
Section: Relationship Between Hyperparameter-optimization and Simulatmentioning
confidence: 99%